(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
This paper develops a novel 3D micro solar-wind hybrid power device for urban street applications. The solar module consists of six trapezoidal silicon solar panels with an efficiency of 21%. An optimized pyramidal design of the photovoltaic module results in 42.5% higher power production compared to flat solar panels by extending the solar exposure time by 4 hours. It was found that at an angular rotation speed of 6–8 rad/s, the surface temperature of the photovoltaic module decreases by 1.3–1.87 °C/min, and the output power increases by increasing the operating voltage by 0.1–0.27 V. A vertical-axis wind turbine prevents overheating of the photovoltaic module surface during the day and allows the use of wind energy to generate additional electricity at night. The device operates effectively at low wind speeds (v = 0.5–2 m/s), which occur during continuous vehicle traffic on highways. The system is equipped with a rechargeable battery, ensuring autonomous operation of the power unit. Potential for widespread implementation of a micro-power system with a capacity of up to several kilowatts is demonstrated